Regulatory Intermediation and Quality Assurance in Higher Education: The Case of the Auditors - King, Roger; Griffiths, Paul; Williams, Ruth (Oxford Review of Education, 2007)
The paper takes the external quality assurance of English universities and colleges as an example of regulation in higher education as undertaken by the Quality Assurance Agency (QAA). Regulatory scholarship generally has been largely disinterested in higher education and the paper applies a